Antioxidant and Anti-inflammatory effect of Graptophyllum pictum (L.) Griff extract Study on SOD and COX-2 serum of experimental hemorrhoids - Azhar, Abu; Riwanto, Ignatius; Nugroho, Eriawan Agung; Susilaningsih, Neni; Prajoko, Yan Wisnu; Budiono, Parish; Prasetyo, Sigit Adi (Medica Hospitalia : Journal of Clinical Medicine, 2020)
Background The 1st, 2nd and small 3rd degree hemorrhoids are non-operatively treated by using anti-inflammatory and plebotonic medicines, high fiber diet and changing lifestyle. Graptophyllum pictum (L.) Griff (GP) is potential to be a hemorrhoid medicine (anti-inflammatory and plebotonic medicine) since its anti-inflammatory effect may be related to antioxidant property. ObjectiveTo elaborate the anti-inflammatory and anti-oxidant effect of GP on experimental hemorrhoid in male Wistar rats. MethodsA Randomized Controlled Trial Post-test only design in hemorrhoid-like rats using croton oil induced into the anus for 30 seconds each day for 3 consecutive days. 14 Wistar rats were randomly allocated into 2 groups. Group 1 got normal saline solution, while group 2 treated with GPE 100mg/Kg bw for 5 consecutive days. On the 9th experimental day, the blood was drawn for Elisa examination of COX-2 and SOD levels. As COX-2 and SOD normally distributed, pool t-test and product moment correlation was used for statistical analysis. Results All of Wistar rats were still alive. COX-2 levels (ng/ml) in the GPE group was 266.28±158.47, was significantly lower compared to control (595.21±68.92) (p=0.000). Serum SOD levels (ng/ml) in the GPE was 77.00±11.0, and was significantly higher than the control 28.00±4.00 (p=0.02). Correlation between COX-2 and SOD serum level was significantly strong negative correlation (p=0,000 and r=-0.842) Conclusions GPE at a dose of 100 mg/kg bw has antioxidant and anti-inflammatory effects on artificial hemorrhoids through decreased COX-2 levels, and elevated SOD levels. There is a strong negative correlation between SOD and COX-2 serum level. KeywordsGraptophyllum pictum, hemorrhoids, Croton oil, COX-2, SOD.